Satisfaction and preference for home delivery pharmaceutical services among patients attending primary care settings in Qatar during COVID-19 pandemic: a cross-sectional study - Ahmed Al Nuaimi; Muhammad Tanveer Alam; Shajitha Thekke Veettil; Jeyaram Illiayaraja Krishnan; Reena Ghazi Alsalmi; Jinsy Jacob; Aly Tamer Mousa; Samah Auni Mesbah Sakallah; Shafqat Mahmood (BMJ Open)
Objectives During the COVID-19 epidemic, due to the high risk associated with travel and group gatherings, the Ministry of Public Health in Qatar introduced home delivery of pharmaceutical services. This study aims to investigate the satisfaction and preferences of patients who used the new home delivery services provided by health centres (HCs).Study design A cross-sectional study was conducted using an exploratory questionnaire to assess patients’ preferences for pharmaceutical delivery services.Settings Primary care.Participants A convenient sample of 604 adults who used the pharmaceutical delivery services was recruited. The study tool measured satisfaction with a set of 11 service evaluation criteria on a Likert scale of 5 grades. The score ranged between 1 for highly dissatisfied and 5 for highly satisfied. A quantitative summary satisfaction score was calculated by summing the satisfaction rating for home delivery on the 11 service evaluation criteria. The final score was adjusted to a maximum of 100 for ease of understanding.Results Results showed that 45.5% of participants were highly satisfied with the overall quality of the home delivery service. Furthermore, 58.9% were willing to recommend the service to others, while only 30.9% considered the delivery cost to be reasonable. Among the factors associated with satisfaction was nationality, where Qatari nationals had a significantly higher mean satisfaction score (89%) compared with expatriates (79.5%).Outcome The satisfaction score exhibited a significant positive trend with age and educational level. Factors such as gender, the time required to access the HCs, frequency of requesting pharmacy service and income categories did not show a significant difference in the satisfaction score.Conclusion The home delivery service is a promising addition to primary care. It may play a crucial role in enhancing accessibility for the beneficiaries reducing unnecessary visits to HCs in the future.